Impactos, dificuldades e avanços na inserção de tecnologias na cultura escolar - Silva, Raul César da (2014)
The technologies are fundamental tools in human evolution. From the beginning the work provided greater efficacy and intellectual productions, distinguished the man from other animals. Running along the various areas of daily activities, are constantly changing and evolution, influencing behaviors, providing opportunities and effecting social change and cultural dynamics. In the area of formal education, represented by the school, the technologies are essential for teaching. Traditional as paper, pencils, board etc., they are already recognized incorporated into the teaching and learning process, as being fundamental. With the advent and access the electronic and microelectronic technologies, the schools are faced of the new reality, whose potential role and the educational needs of reflections. These new features, represented at schools with greater frequency for televisions, computers and accessories, are they gradually integrated into this institution. In this process, one must consider that these instruments are contaminated by the interests of capitalism through the mass media, using technological resources and its ability to integrate multiple languages, seducing for consumption. In this sense the formal education beyond this challenge need to consider the influence that the mass media have on students. The impacts are clearly perceived in the relationship of students with formal knowledge. Several initiatives, government and teachers are held to find the place and the role of technology in education. Many of them collide on personal, institutional and lack of theoretical depth limits. In this sense the continuing education are fundamental to this debate. This research was based on the experiences of the public schools in Paraná and held in high schools the city of Francisco Beltrão. We seek to identify how they have been used technological resources available at the school, limitations, difficulties and results. We discuss also the differences in the use and control of these resources between teachers and students. As we seek to broaden the debate curricular and social issues that affect the teaching and learning process.